Heidegger e Chillida. Un dialogo sullo spazio - Stefano Esengrini (Aisthesis, 2012)
Heidegger’s encounter with art determines a decisive turning point inside his own path of thinking. Klee and Cézanne in painting and Chillida in sculpture are just some of the numerous artists Heidegger met and studied since the Thirties. These artists contributed to establish a lively dialogue with the German philosopher on the main questions concerning their works. Space becomes the theme Heidegger and Chillida investigate as the origin of the work of art – in this case, of the sculptural or, better, plastic one. As a matter of fact, the space Heidegger and Chillida refer to has nothing to do with space as conceived by modern science; therefore space is thought in terms of place where man dwells, is. In this perspective art and thought show themselves as the knowledge capable of founding a place, a space-and-time for man’s dwelling on the earth, under the sky.